Ultrahigh transverse thermoelectric power factor in flexible Weyl semimetal WTe2 - Pan, Yu; He, Bin; Helm, Toni; Chen, Dong; Schnelle, Walter; Felser, Claudia (Nature Communications, 2022)
Topological semimetals are well known for their interesting physical properties, while their mechanical properties have rarely received attention. With the increasing demand for flexible electronics, we explore the great potential of the van der Waals bonded Weyl semimetal WTe2 for flexible thermoelectric applications. We find that WTe2 single crystals have an ultrahigh Nernst power factor of 3 Wm−1K−2, which outperforms the conventional Seebeck power factors of the state-of-the-art thermoelectric semiconductors by 2–3 orders of magnitude. A unique band structure that hosts compensated electrons and holes with extremely high mobilities is the primary mechanism for this huge Nernst power factor. Moreover, a large Ettingshausen signal of 5 × 10−5 KA−1m is observed at 23.1 K and 9 T. In this work, the combination of the exceptional Nernst–Ettingshausen performance and excellent mechanical transformative ability of WTe2 would be instructive for flexible micro-/nano-thermoelectric devices.
CRIS-Team Scopus Importer:2023-03-20